1972
DOI: 10.1177/003072707200700102
|View full text |Cite
|
Sign up to set email alerts
|

Potato agronomy in a changing industry

Abstract: The extension of potato culture from Peru to North America, Europe and the rest of the world has been accompanied by the development of a variety of production systems. With the intensification of potato production in many countries, the available genetic resources of the plant are being severely stretched. This may be why experimental departures from standard husbandry do not always give the advantages expected. Potato agronomy, nevertheless, is in the throes of change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…In general, net returns increased with the use of heavier seed tubers and, on average, returns from using 105 g seed tubers were 19% higher than from using 35 g seed tubers. This agrees with the statement of Scott & Younger (1972) that large seed was most valuable to early growers because of the early yield advantage that it conferred. They were referring to equal numbers of seed tubers of different sizes, whereas our data show that when each seed-tuber weight is planted at its own optimum density there is an advantage in using large seed tubers.…”
Section: Optimum Tuber Densitiessupporting
confidence: 91%
“…In general, net returns increased with the use of heavier seed tubers and, on average, returns from using 105 g seed tubers were 19% higher than from using 35 g seed tubers. This agrees with the statement of Scott & Younger (1972) that large seed was most valuable to early growers because of the early yield advantage that it conferred. They were referring to equal numbers of seed tubers of different sizes, whereas our data show that when each seed-tuber weight is planted at its own optimum density there is an advantage in using large seed tubers.…”
Section: Optimum Tuber Densitiessupporting
confidence: 91%
“…The narrowest within-row spacings occurred on wider rows and effects of row width were generally detected earlier than effects of planting density. In 1972 when high numbers of stems were achieved, wider rows reduced the number of stems resulting from high planting densities; this result reflects very intense competition since number of stems per seed tuber is determined early in growth and is usually un- affected by within-row spacing (Scott & Younger, 1972). Effects of planting density were not apparent until early June and effects on plant size and morphology persisted and sometimes increased.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments involving * Present address: National Koot Crop Research marked changes in spatial arrangement have Institute, Irish Potato Research, Vom, Jos, Nigeria. generally indicated that potato crops are remark-0. P. IFENKWE AND E. J. ALLEN ably tolerant of such changes (Scott & Younger, 1972), so there is reasonable expectation that rows wider than 91 cm will not produce large reductions in yield. The ability of potato crops to compensate for wider row spacing is primarily dependent on the production of a complete leaf cover, so that wetter environments in which leaf growth is more extensive are likely to be less sensitive to large changes in row width than drier areas.…”
Section: Introductionmentioning
confidence: 99%
“…asserted (e.g. Scott & Younger, 1972) that a long sprouting period is essential for good yields in Almost all the seed used for early potato pro-early potato production but few, convincing data duction in U.K. is sprouted for some time (Potato are available to support the practice. With the Marketing Board, 1968).…”
Section: Introductionmentioning
confidence: 99%